Synthesis and cellular impact of diene-ruthenium(II) complexes: a new class of organoruthenium anticancer agents - Kasper, Christine; Alborzinia, Hamed; Can, Suzan; Kitanovic, Igor; Wölfl, Stefan (Journal of inorganic biochemistry, 2012)
The cytostatic properties and cellular effects of novel diene-ruthenium(II) complexes of the types OC-6-13-[RuCl2(pp)(cod)] 1-5 (pp=2,2′-bipyridyl (bpy), phen=1,10-phenanthroline (phen), 5,6-dimethylphenanthroline (5,6-Me2phen), dipyrido[3,2-d:2′,3′-f]quinoxaline (dpq), ethylenediamine (en)) and OC-6-24-[RuCl{(Me2N)2CS}(pp)(cod)](CF3SO3) 6-8 (pp=phen, 5,6-Me2phen, dpq) have been studied for the human cancer cell lines MCF-7 and HT-29 and for Jurkat leukemia cells. CD spectra indicate that 7 causes a massive distortion of the CT DNA B double helix toward the A form. Whereas the neutral complexes 1, 2 and 5 exhibit only modest antiproliferative activity toward MCF-7 and HT-29 cells, the monocationic complexes are significantly more active, in particular the DNA-distorting complex 7 with its IC50 values of 0.73 and 0.42μM, respectively. As established by online monitoring with a cell-based sensor chip, this potent 5,6-Me2phen complex invokes dose-dependent decreases in MCF-7 cellular respiration and extracellular acidification rates and causes a time-delayed decrease in the impedance of the cell layers, that can be ascribed to cell death. Treatment of Jurkat cells with 7 leads to high concentrations of reactive oxygen species and the induction of apoptosis. The pronounced dose-dependent inhibition of oxygen consumption by isolated mice mitochondria indicates the involvement of an intrinsic mitochondrial pathway in the programmed cell death process.